Capturing tensile size-dependency in polymer nanofiber elasticity. (February 2015) - Yuan, Bo; Wang, Jun; Han, Ray P.S.
Abstract: As the name implies, tensile size-dependency refers to the size-dependent response under uniaxial tension. It defers markedly from bending size-dependency in terms of onset and magnitude of the size-dependent response; the former begins earlier but rises to a smaller value than the latter. Experimentally, tensile size-dependent behavior is much harder to capture than its bending counterpart. This is also true in the computational effort; bending size-dependency models are more prevalent and well-developed. Indeed, many have questioned the existence of tensile size-dependency. However, recent experiments seem to support the existence of this phenomenon. Current strain gradient elasticity theories can accurately predict bending size-dependency but are unable to track tensile size-dependency. To rectify this deficiency a higher-order strain gradient elasticity model is constructed by including the second gradient of the strain into the deformation energy. Tensile experiments involving 10 wt% polycaprolactone nanofibers are performed to calibrate and verify our model. The results reveal that for the selected nanofibers, their size-dependency begins when their diameters reduce to 600 nm and below. Further, their characteristic length-scale parameter is found to be 1095.8 nm.